What drives cross-border M&As in commercial banking? - Gulamhussen, M. A.; Hennart, J. F.; Pinheiro, C. (Journal of Banking and Finance, 2016)
Using a gravity model, we analyze the determinants of the probability that commercial banks in 89 acquiring countries and 118 target countries will undertake M&As over a 30-year period (1981–2010) and of the value of these M&As. We find that the value of cross-border M&As increases with the size of the acquiring country, and that both the probability and value of M&As vary positively with the depth of the financial market in acquirer countries and the presence of corporate and non-corporate customers from acquiring countries in target countries, and negatively with the geographic, psychic, and time zone distances between acquirer and target countries. Our study highlights the role of non-corporate customers and of psychic distance in the cross-border expansion of commercial banks through M&As.